A evasão de profissionais qualificados do Estado do Rio Grande do Sul e a relação com a gestão estratégica de pessoas - Giongo, Andressa Pereira (Universidade do Vale do Rio dos Sinos, 2023)
In the knowledge society, human assets have gained significant importance within organizations, given their ability to transform knowledge and experiences into relevant solutions and contributions to the business environment, driving organizational growth. The main objective of this study is to understand the phenomenon of skilled professionals' attrition in the state of Rio Grande do Sul (RS) and its relationship with people management. The research employed a mixed-method approach, starting with a pilot survey involving 101 respondents who provided their perceptions on the subject, followed by a qualitative research phase with 22 participants. Among them were professionals who had emigrated for professional reasons, those intending to do so, executives representing companies based in RS, and headhunters. The data analysis was conducted using NVivo software. The collected results demonstrate that the interviewees perceive the attrition of skilled professionals occurring in RS, with the main reasons being individual motivations of the professionals. These motivations are linked to the pursuit of new career opportunities and challenges, along with better financial recognition. Other motivations for attrition include characteristics of the business environment and an unfavorable economic climate. In light of this context, a value proposition is presented as a means to attract and retain qualified professionals, accompanied by managerial recommendations to facilitate its implementation. Consequently, this study aims to contribute to public entities, organizations, and human resource management areas that seek to attract and retain skilled professionals.
Keywords: Evasão; Talentos; Gestão Estratégica de Pessoas; Proposta de valor; Brain drain; Talents; Strategic People Management; Value proposition; ACCNPQ::Ciências Sociais Aplicadas::Administração